Catalytic effect of ammonia-containing species on water splitting during electrodialysis with ion-exchange membranes. (10th March 2019) - Rybalkina, O.A.; Tsygurina, K.A.; Melnikova, E.D.; Pourcelly, G.; Nikonenko, V.V.; Pismenskaya, N.D.
Abstract: It is known that some components of the bathing solution can enhance water splitting at depleted solution/ion-exchange membrane interface via protonation/deprotonation reactions with water. In this paper, we show that not only the presence of such components is important, but also a mechanism ensuring their sufficiently high concentration near the membrane surface. A comparative study of the electrochemical behavior of a Neosepta ® homogeneous cation-exchange CMX and an anion-exchange AMX membranes (Astom, Japan) in 0.02 M KCl or 0.02 M NH4 Cl solutions is carried out. The NH4 + /NH3 couple is an effective catalyst of water splitting. The deprotonation reaction rate constant of the NH4 + ions, which limits the rate of water splitting, is about 10 s −1 . It is almost 6 orders of magnitude greater than the rate constant for direct water dissociation in free solution. A comprehensive electrochemical characterization of the membrane systems is made: voltammetry, chronopotentiometry, electrochemical impedancemetry, and pH-metry (including color indication of the pH of the membrane internal solution). It is found that the water splitting rate at the interface of the AMX membrane in the NH4 Cl solution is essentially higher than in the KCl solution. The difference in the rates of this reaction in KCl and NH4 Cl solutions at the CMX membrane is insignificant. The reason for the weak effect of the NH4 + /NH3 couple on the rate of water splitting at the CMX membrane is that the concentration of both NH4 + and NH3 species is very low near its surface if the current density is close to or higher than its limiting value. As for the AMX membrane, we show that the ammonia-containing species can be transported to its depleted surface from the enriched solution by back "facilitated" diffusion through the membrane and this transport plays a crucial role in the occurrence of the rapid water splitting.